The Effect of Implementing the Problem-Based Learning Model Assisted by the Kemendikdasmen Virtual Web Lab on Elementary School Students’ Problem-Solving Skills in Science Learning - Ashfa Nurul Mahmudah; Hisny Fajrussalam; Nenden Permas Hikmatunisa (Vifada Journal of Education, 2026)
This study aims to examine the effect of implementing the Problem-Based Learning model assisted by the Kemendikdasmen Virtual Web Lab on elementary school students’ problem-solving skills in science learning. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The sample consisted of 24 students in the experimental class and 26 students in the control class. Data were collected through problem-solving ability tests administered as a pretest and posttest. The data were analyzed using normality tests, homogeneity tests, an Independent Samples t-test, and N-Gain analysis. The results showed a significant difference between the experimental and control classes, with a significance value of 0.039 (< 0.05). Furthermore, the N-Gain score of the experimental class was 0.3204, which falls into the moderate category, and was higher than that of the control class, which was 0.2090 and categorized as low. These findings indicate that the implementation of the Problem-Based Learning model assisted by the Kemendikdasmen Virtual Web Lab is more effective in improving students’ problem-solving skills than conventional learning models. This is because the model provides students with opportunities to actively engage in inquiry and problem-solving processes. Therefore, the Problem-Based Learning model assisted by the Kemendikdasmen Virtual Web Lab can be considered an alternative science learning model in elementary schools to enhance students’ problem-solving skills